School Culture and Leadership Behavior as Predictors of Job Satisfaction among Private Elementary School Teachers: An Explanatory Sequential Design - Huda, Muhammad; Alderite, Thelma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Job satisfaction is a pivotal element influencing the efficiency and effectiveness of organizations that assess the degree to which someone views their job favorable or unfavorable. This study aimed to examine the influence of school culture and leadership behavior on the job satisfaction of teachers. This research employed mixed methods research, specifically explanatory sequential design. The research took place in Semarang City, Central Java Province, Indonesia. Private elementary school teachers were surveyed using the purposive sampling technique regarding the level of school culture, leadership behavior, and job satisfaction. Then, the teachers were interviewed through IDI and FGD to confirm the salient points. Results were analyzed using mean and regression in the quantitative strand; and thematic data analysis in the qualitative strand. The results showed that there was as very high status of school culture, which means always evident, while perceived leadership behavior was rated very high, which means it is always observed, and job satisfaction was rated as very high, which means it is always manifested. Moreover, the combined influence of the two independent variables, school culture, and leadership behavior have significant influence on the job satisfaction of teachers. Further, confirmed very high rating and confirmed combined significant influence were the common essential themes. Furthermore, connecting-confirmations were the nature of data integration.